Cascade testing as the missing link in cancer prevention among Lynch syndrome families - Lea Godino; Giulia Erini; Giovanni Innella; Sara Miccoli; Simona Ferrari; Pamela Magini; Luca Caramanna; Martina Preite; Veronica Simoni; Daniela Turchetti (Familial Cancer, 2026)

Generative artificial intelligence and marine ecological monitoring - Luciano Ortenzi; Jacopo Aguzzi; Damianos Chatzievangelou; Eugenio Nerio Nemmi; Michele Ferrari; Ivan Masmitja; Morane Clavel-Henry; Nixon Bahamon; Nathan J. Robinson; Giacomo Picardi; Paula Espina; Simona Violino; et al. (Environmental Modelling & Software, 2026)

Green hydrogen production in methylcyclohexane dehydrogenation by ceramic membrane reactor as net-zero approach: Optimisation via digital twin methodology - Tara Torabi; Maria-Chiara Ferrari; Simona Liguori; Kamran Ghasemzadeh (Chemical Engineering Journal, 2025)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Digital biomarkers and sex impacts in Alzheimer’s disease management — potential utility for innovative 3P medicine approach - Robbert L. Harms; Alberto Ferrari; Irene B. Meier; Julie Martinkova; Enrico Santus; Nicola Marino; Davide Cirillo; Simona Mellino; Silvina Catuara Solarz; Ioannis Tarnanas; Cassandra Szoeke; Jakub Hort; et al. (EPMA Journal, 2022)
Digital biomarkers are defined as objective, quantifiable physiological and behavioral data that are collected and measured by means of digital devices. Their use has revolutionized clinical research by enabling high-frequency, longitudinal, and sensitive measurements. In the field of neurodegenerative diseases, an example of a digital biomarker-based technology is instrumental activities of daily living (iADL) digital medical application, a predictive biomarker of conversion from mild cognitive impairment (MCI) due to Alzheimer’s disease (AD) to dementia due to AD in individuals aged 55 + . Digital biomarkers show promise to transform clinical practice. Nevertheless, their use may be affected by variables such as demographics, genetics, and phenotype. Among these factors, sex is particularly important in Alzheimer’s, where men and women present with different symptoms and progression patterns that impact diagnosis. In this study, we explore sex differences in Altoida’s digital medical application in a sample of 568 subjects consisting of a clinical dataset (MCI and dementia due to AD) and a healthy population. We found that a biological sex-classifier, built on digital biomarker features captured using Altoida’s application, achieved a 75% ROC-AUC (receiver operating characteristic — area under curve) performance in predicting biological sex in healthy individuals, indicating significant differences in neurocognitive performance signatures between males and females. The performance dropped when we applied this classifier to more advanced stages on the AD continuum, including MCI and dementia, suggesting that sex differences might be disease-stage dependent. Our results indicate that neurocognitive performance signatures built on data from digital biomarker features are different between men and women. These results stress the need to integrate traditional approaches to dementia research with digital biomarker technologies and personalized medicine perspectives to achieve more precise predictive diagnostics, targeted prevention, and customized treatment of cognitive decline.

The paramount role of cytokines and chemokines in papillary thyroid cancer: a review and experimental results - Poupak Fallahi; Silvia Martina Ferrari; Simona Piaggi; Michaela Luconi; Giulia Cantini; Stefania Gelmini; Giusy Elia; Ilaria Ruffilli; Alessandro Antonelli (Immunologic Research, 2018)

Trans-splicing of plastid rps12 transcripts, mediated by AtPPR4, is essential for embryo patterning in Arabidopsis thaliana - Luca Tadini; Roberto Ferrari; Marie-Kristin Lehniger; Chiara Mizzotti; Fabio Moratti; Francesca Resentini; Monica Colombo; Alex Costa; Simona Masiero; Paolo Pesaresi (Planta, 2018)

Waste treatment: an environmental, economic and social analysis with a new group fuzzy PROMETHEE approach - Francesco Lolli; Alessio Ishizaka; Rita Gamberini; Bianca Rimini; Anna Maria Ferrari; Simona Marinelli; Roberto Savazza (Clean Technologies and Environmental Policy, 2016)

A 12.4 Mb direct duplication in 19q12-q13 in a boy with cardiac and CNS malformations and developmental delay - Licia Lugli; Michela Malacarne; Simona Cavani; Mauro Pierluigi; Fabrizio Ferrari; Antonio Percesepe (Journal of Applied Genetics, 2011)

Selenite resistant rhizobacteria stimulate SeO3 2– phytoextraction by Brassica juncea in bioaugmented water-filtering artificial beds - Silvia Lampis; Anita Ferrari; A. Cristina F. Cunha-Queda; Paula Alvarenga; Simona Di Gregorio; Giovanni Vallini (Environmental Science and Pollution Research, 2009)

Fetal DNA detection in maternal plasma throughout gestation - Silvia Galbiati; Maddalena Smid; Dania Gambini; Augusto Ferrari; Gabriella Restagno; Elsa Viora; Mario Campogrande; Simona Bastonero; Marco Pagliano; Stefano Calza; Maurizio Ferrari; Laura Cremonesi (Human Genetics, 2005)

Inhibition of left ventricular remodelling preserves chamber systolic function in pressure-overloaded mice - Giuseppe Marano; Sergio Palazzesi; Alessandro Vergari; Liviana Catalano; Simona Gaudi; Claudia Testa; Rossella Canese; Giulia Carpinelli; Franca Podo; Alberto U. Ferrari (Pflügers Archiv - European Journal of Physiology, 2003)